Galacticos Futsal / Mohd Faqrulrazi Illa ... [et al.] - Illa, Mohd Faqrulrazi; Samsudin, Mohd Ezzwan Shah; Mohamad Jamil, Shahruladzli; Nordin, Shahrul; Hassan, Wan Mohd Zulkhairi (Faculty of Applied Sciences, 2006)
Futsal is the main nature of our business. The enterprise consists of 5 managers which include the general manager, the marketing manager, the administration manager, and financial manager and operational managers. Each manager has their responsibilities which suits their qualifications and skills.